HUBUNGAN FREKUENSI KONSUMSI MAKANAN CEPAT SAJI, ASUPAN KALSIUM, MAGNESIUM, DAN IMT/U DENGAN SIKLUS MENSTRUASI PADA REMAJA DI SMAN 2 GUNUNGPUTRI TAHUN 2021 - Shella Yehovani (2021)
Menstruation is one of the processes of growth and development of a woman who has experienced the maturation of the reproductive organs. Along with the process of growth and development, hormonal changes can occur in the body that can make a person susceptible to menstrual cycle disorders. Hormone balance can be influenced by many factors, some of which are consumption of fast food, intake of calcium and magnesium and nutritional status. The purpose of this study is to know and analyze the relationship between fast food consumption freuquency, intake of calcium, magnesium and BMI for age with the menstrual cycle in adolescent girls at SMAN 2 Gunungputri. This study is a quantitative study that uses an analytic observational method with a cross sectional design. The sampling technique is stratified random sampling with total sample of 55 respondents that was taken randomly. All of the data taken using questionnaires, FFQ (Food Frequency Questionnaire) forms, and SQ FFQ (Semiquantitative Food Frequency Questionnaire) forms. The statistical test uses the chi-square test. Based on bivariate analysis, there is a relationship between fast food consumption frequency with menstrual cycle in adolescent girls at SMAN 2 Gunungputri (p-value = 0.009) and there is no relationship between calcium intake (p-value = 0.170), magnesium intake (p-value = 0,948) and BMI for age (p-value = 0,938) with menstrual cycles in adolescent girls at SMAN 2 Gunungputri.